Análise das políticas públicas para a inclusão social das mulheres na Ciência, Tecnologia e Inovação (CTI): formação, acesso e permanência - de Oliveira Benedito, Beatriz [UNESP]; da Silva, Elaine [UNESP]; Woida, Luana Maia [UNESP]; de Carvalho Pazin Vitoriano, Marcia Cristina [UNESP] (Revista Ibero-Americana de Estudos em Educacao, 2025)
The general objective of this work was to analyze public policies regarding the training, access and permanence of women in science, technology and innovation in Latin America. This is a qualitative and descriptive study, delineated by documentary research, aiming at understanding the characteristics of the studied phenomenon. Content analysis was used as a method and categorical analysis as a technique. The results indicate that the measures developed by Latin American countries follow three axes: encouraging training in science, technology, engineering and mathematics, since the earliest childhood stages; access and permanence in power positions and scientific careers; inclusion of the ‘gender’ perspective in research and innovation contente.